2005
DOI: 10.1097/01.prs.0000165077.40778.00
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative Topographical Evaluation of the Orbitozygomatic Complex

Abstract: Low variability between measurements within the same individual (<1.5 mm) underscores the reliability of the chosen landmarks and techniques in the determination of orbitozygomatic complex position. Second, the complex occupies a consistent position among individuals, as shown by the low intersubject variability. Third, there is no statistically significant difference in the position of the complex, in any plane of space, between the left and right sides of the face. Thus, the authors' method may be used to de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
16
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 8 publications
1
16
0
Order By: Relevance
“…The interobserver variability ranged from 2.9 to 9.1 mm (3% to 9.6%). 5 Another study of sagittal orbital anthropometry discerned 0.2-mm exactness of the orbital anthropometer that, however, differed significantly from the semiautomatic anthropometric caliper used in this study. Further, 1% intraob- Semiautomatic Anthropometry server error and mostly nonsignificant interobserver differences were reported.…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…The interobserver variability ranged from 2.9 to 9.1 mm (3% to 9.6%). 5 Another study of sagittal orbital anthropometry discerned 0.2-mm exactness of the orbital anthropometer that, however, differed significantly from the semiautomatic anthropometric caliper used in this study. Further, 1% intraob- Semiautomatic Anthropometry server error and mostly nonsignificant interobserver differences were reported.…”
Section: Discussionmentioning
confidence: 85%
“…The refinement of the algorithm will provide reliable estimation of the accuracy of positioning of several surgical techniques of fracture repositioning and fixation. 5 Using the Ophistocranion as dorsal landmark (z-axis definition) was considered slightly less exact and reproducible as the tragus.…”
Section: Discussionmentioning
confidence: 99%
“…Unsatisfactory outcomes often result from undetected ZMC axial rotations, such as the greater wind of the sphenoid. 4,14 We adopted the reference points described by Donald 10 and modified by Czerwinski et al, 7 who validated that the system is reliable and simple; furthermore, they confirmed that the system is suitable for describing the relative position of ZMC by using only 6 references, which are zy, n, mz, or, v, and op, and direct measurement. Direct anthropometry may lead to patient discomfort and is time consuming; furthermore, the relationship between skeletal and soft tissue cannot be defined and evaluated clearly.…”
Section: Discussionmentioning
confidence: 91%
“…Quantitatively evaluating the topography of the ZMC is another approach for assessing ZMC fractures associated with soft tissue deformities. 7,8 However, this approach is not widely applied because it is time consuming and is marred by motion artifacts; furthermore, it entails performing inconvenient repetitive measurements and produces poor evaluation outcomes for bony parts. Three-dimensional digital photogrammetry is widely applied in many institutes.…”
mentioning
confidence: 99%
“…Historically, indirect soft-tissue anthropometric points and direct cephalometric points of the bony skull were used for measurement of the facial skeleton. The mean intra-subject variability for setting these landmarks lies between 0.7 mm and 1.5 mm 11,12 . Needle, caliper and tape measures are now obsolete, and, increasingly, modern computer-aided methods are used 6,19 .…”
Section: Discussionmentioning
confidence: 99%